2007
DOI: 10.1111/j.1574-695x.2006.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 2-day-old and 14-day-old chicken colonization models forCampylobacter jejuni

Abstract: In this study, we compared two types of chicken infection models for Campylobacter jejuni in terms of infectious dose required to colonize the chickens and the susceptibility of chickens of different ages to persistent colonization by C. jejuni. In one model, chickens at day 2 posthatching were used, and in the other, 14-day-old chickens were used. The minimum C. jejuni cell number required to colonize 14-day-old chickens was 5 Â 10 4 cells, and that for 2-day-old chickens was 5 Â 10 3 . The ability of various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
1
31
1
1
Order By: Relevance
“…A similar change of the predominant clone [13] and the colonisation phenotypes [20] in chickens were reported. Humphrey et al [5] have reported that a small proportion of FQresistant Campylobacter spp.…”
supporting
confidence: 73%
“…A similar change of the predominant clone [13] and the colonisation phenotypes [20] in chickens were reported. Humphrey et al [5] have reported that a small proportion of FQresistant Campylobacter spp.…”
supporting
confidence: 73%
“…The cecum is more susceptible to C. jejuni colonization than other tissues including spleen, lung, heart, and liver in the chicken (Knudsen et al, 2006). Campylobacter jejuni isolated from both humans and chickens are capable of colonizing chickens (Stern et al, 1990;Knudsen et al, 2006;Ringoir et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of introduction of Campylobacter can be high throughout the rearing period, but it could also be hypothesized that this risk may increase over time. Another possibility is that young chicks are less susceptible, as indicated by Ringoir et al (13) and Sahin et al (14), who demonstrated that age and maternally derived immunity had an effect on susceptibility. More insight into the underlying mechanism of this phenomenon may provide clues for prevention of Campylobacter colonization.…”
Section: Discussionmentioning
confidence: 99%